Virtù e valores no pensamento de Maquiavel - Flavia Roberta Benevenuto de Souza (2003)
This work approaches the subject of 'virtú' in the Machiavelli´s thinking, opposing it to the virtue that belongs to the tradition. This opposition opens a discussion between the elements present in The Prince as well, in Discorsi and the Chirstians values of Machiavellian time.